The Use Of Fixed Assets Management System In Souvenir Centre - Elisa Farida; G. Freddy Koeswoyo; Erdhi Widyarto Nugroho (Soegijapranata Catholic University, 2021)
Assets have a large role in shoring up a business process in a particular entity. Without fixed assets, a business will be difficult to do its business processes well. Fixed assets owned by Souvenir Centre Group 58 have not been well recorded, from the physical amount or in accounting records. Often the recording of assets manually causes problems due to the possibility of human error. Recording the depreciation of an asset is also a necessity of an entity that runs business processes. Therefore, an application is needed that can replace the manual process to be systemized. The aim of the research to be conducted is to design and develop and implement a fixed asset inventory system at a central store by QR-Code-based